Solid suspension and gas dispersion in gas-solid-liquid stirred vessels with high solid concentration / Meysam Davoody - Meysam, Davoody (2017)
Mechanically agitated vessels are used widely for gas-liquid-solid mixing operations in processing plants. In such systems, increase in solid concentration increases the energy required to suspend the solids off the tank bottom. Therefore, improving agitator energy efficiency is essential for operating at high solids concentrations. Most of previous studies are limited to low solids concentrations in solid-liquid systems. Therefore, it is imperative to determine the best possible impeller and tank geometries, and optimum operating conditions for tanks handling high concentration slurries, such as those found in mineral processing plants. This study aims at proposing optimum industrial agitator designs for systems handling high concentration slurries (up to 40% v/v) in the presence of gas. In this regard, a combination of both operational (solid concentration) and design (impeller type and baffling condition) parameters were considered for investigating specific impeller power (Pj/Ms) and gas hold-up. The apparatus utilized in this study includes a 0.4 m diameter flat bottom cylindrical perspex tank. The agitation was provided by a shaft which was placed in vertical axis of the tank and driven by a 3.0 kW motor. The power efficiency factor (εjsg-1 (kg/W)) serves as an indication of the quantity of solid particles that could be suspended per unit of power consumed by impeller. Accordingly, it was found that the εjsg-1 values can be maximized by operating the mixing tank with an optimum range of solids concentration, which is around Cv = 0.2 - 0.3 v/v for the systems studied in this work. It was observed that larger diameter mixed flow impellers were more energy efficient when the tank was operated under aerated condition with an optimum concentration of solids. Increase in particle size resulted in lower εjsg-1 values and this phenomenon was more prominent in unbaffled tanks. Another term, known as baffling efficiency factor, ‘R’, was used to study how baffle removal influences the energy efficiency of impellers in three-phase systems. It was observed that absence of baffles could exert negative effects on energy efficiency of axial- and mixed-flow impellers at particular operating conditions. The investigations also included the effect of baffle removal on solid dispersion. Gas holdup, Sauter mean bubble diameter (d32), and gas-liquid interfacial area (ɑg-l) were also studied. The results indicated that d32 values decrease with an increase in particle size and solids concentration. Then, an optimum solids concentration was identified at which the performance of the impeller expressed in terms of power efficiency and ability to generate sufficient gas-liquid interfacial area is maximized. Mathematical models were developed to predict the optimum solids concentration, d32, and ɑg-l, and their predictions exhibited reasonable agreement with the experimental results. In the last part of this paper, an example is shown to highlight the advantages of implementing the optimization strategies proposed in this work.